Drain-free neck dissection: the use of Artiss fibrin sealant. Issue 5 (26th May 2023) - Bahgat, M; Lim, K H; Lester, S
Abstract: Objective: To study the safety and efficacy of Artiss fibrin sealant in lateral neck dissection, focusing on drain retention time, length of hospital stay and post-operative complications. Methods: A retrospective review was conducted of patients who underwent neck dissection in a UK hospital over a 12-month period. Results: Twenty-three patients were identified; 13 patients had Artiss and a drain, 10 patients had Artiss only. All drains were removed by post-operative day 2. No post-operative fluid collections or complications were recorded. Patients who had Artiss only without a drain were discharged on post-operative day 1. Conclusion: The use of Artiss reduced the drain retention time and hospital stay, with no post-operative complications. Neck dissection can be safely undertaken with no drain, and can potentially be carried out as a day-case procedure, with the application of Artiss. These findings benefit patients and the National Health Service by improving the patient journey and reducing overall costs.